Role of energy charge and AMP-activated protein kinase in adipocytes in the control of body fat stores - Rossmeisl, M; Flachs, P; Brauner, P; Sponarova, J; Matejkova, O; Prazak, T; Ruzickova, J; Bardova, K; Kuda, O; Kopecky, J (International journal of obesity and related metabolic disorders, 2004)
As indicated by in vitro studies, both lipogenesis and lipolysis in adipocytes depend on the cellular ATP levels. Ectopic expression of mitochondrial uncoupling protein 1 (UCP1) in the white adipose tissue of the aP2-Ucp1 transgenic mice reduced obesity induced by genetic or dietary manipulations. Furthermore, respiratory uncoupling lowered the cellular energy charge in adipocytes, while the synthesis of fatty acids (FA) was inhibited and their oxidation increased. Importantly, the complex metabolic changes triggered by ectopic UCP1 were associated with the activation of AMP-activated protein kinase (AMPK), a metabolic master switch, in adipocytes. Effects of several typical treatments that reduce adiposity, such as administration of leptin, beta-adrenoceptor agonists, bezafibrate, dietary n-3 polyunsaturated FA or fasting, can be compared with a phenotype of the aP2-Ucp1 mice. These situations generally lead to the upregulation of mitochondrial UCPs and suppression of the cellular energy charge and FA synthesis in adipocytes. On the other hand, FA oxidation is increased. Moreover, it has been shown that AMPK in adipocytes can be activated by adipocyte-derived hormones leptin and adiponectin, and also by insulin-sensitizes thiazolidinediones. Thus, it is evident that metabolism of adipose tissue itself is important for the control of body fat content and that the cellular energy charge and AMPK are involved in the control of lipid metabolism in adipocytes. The reciprocal link between synthesis and oxidation of FA in adipocytes represents a prospective target for the new treatment strategies aimed at reducing obesity.
Keywords: energetický metabolismus; AMP-Activated Protein Kinases; Choristoma; Mitochondria; protein-serin-threoninkinasy; Obesity; Uncoupling Protein 1; Protein Serine-Threonine Kinases; tuková tkáň; membránové proteiny; Membrane Proteins; obezita; Adipocytes; iontové kanály; Models, Biological; mitochondriální proteiny; Multienzyme Complexes; Ion Channels; Carrier Proteins; Mitochondrial Proteins; tukové buňky; Animals; lidé; Energy Metabolism; biologické modely; Adipose Tissue; choristom; myši transgenní; uncoupling protein 1; Humans; zvířata; Mice, Transgenic; myši; multienzymové komplexy; Mice; proteinkinasy aktivované AMP; transportní proteiny; mitochondrie